2018
DOI: 10.1007/s12026-018-9045-0
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular mimicry, genetic homology, and gene sharing proteomic “molecular fingerprints” using an EBV (Epstein-Barr virus)-derived microarray as a potential diagnostic method in autoimmune disease

Abstract: EBV (Epstein-Barr Virus) and other human DNA viruses are associated with autoimmune syndromes in epidemiologic studies. In this work, immunoglobulin G response to EBV-encoded proteins which share regions with human immune response proteins from the human host including ZEBRA (BZLF-1 encoded protein), BALF-2 recombinase expressed primarily during the viral lytic replication cycle, and EBNA-1 (Epstein-Barr Virus Nuclear Antigen) expressed during the viral latency cycle respectively were characterized using a las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In general, viral infections can interact with the host immune system through several mechanisms which ultimately lead to the loss of tolerance, the production of autoantibodies, the tissue deposition of immune complexes and consequent tissue damage. These are: structural or functional molecular mimicry, epitope spreading, superantigen production, bystander activation, altered apoptosis and clearance deficit, epigenetic factors, persistent or recurrent viral infection, and innate immunity activation with type I IFN production [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: General Mechanisms Of Virus-induced Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, viral infections can interact with the host immune system through several mechanisms which ultimately lead to the loss of tolerance, the production of autoantibodies, the tissue deposition of immune complexes and consequent tissue damage. These are: structural or functional molecular mimicry, epitope spreading, superantigen production, bystander activation, altered apoptosis and clearance deficit, epigenetic factors, persistent or recurrent viral infection, and innate immunity activation with type I IFN production [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: General Mechanisms Of Virus-induced Autoimmunitymentioning
confidence: 99%
“…Molecular mimicry Viral antigens with structural similarity with self-antigens can be presented to and activate autoreactive T-lymphocytes. [8,9,[14][15][16][17][18] Epitope-spreading Over time, persistent viral infection elicits autoantibodies directed not only towards initial antigens but also multiple epitopes of the same antigens or even different antigens, increasing breadth of immune response.…”
Section: Mechanism Description Referencesmentioning
confidence: 99%
“…Peptide microarrays are a recently developed proteomic analysis method with a similar sensitivity to those of traditional methods [25]. Since various epitopes of viral antigens or autoantibodies often need to be analyzed simultaneously, this method is used to screen peptides related to autoimmune diseases [18,26,27]. The results of the present comprehensive peptide microarray screening of 2440 peptides selected based on previous literature [8] revealed CMV, HSV, MAG, HIF-1 alpha, and EBV-related peptides as possible candidates for discriminating CNS inflammatory demyelinating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a recent study has demonstrated that EBNA2, an EBV/latent protein colocalizes with autoimmune risk loci in B cells of several autoimmune diseases including SLE, strongly suggesting that EBV contributes to the origin of the genetic risk in these disorders (29). Evidences linking EBV and SSc have been also reported, since EBV latent antigens and high titers of EBV antibodies have been detected more often in SSc patients (30)(31)(32). Interestingly, it has been shown that B cells from healthy donor upon EBV transformation were able to produce anti-topoisomerase antibodies (Scl-70) strongly supporting the notion that production of autoantibodies might be directly related to EBV infection in SSc (33).…”
Section: Introductionmentioning
confidence: 99%